Forced convection heat transfer of aviation kerosene enhanced by electric field in a circular channel. (October 2021) - Qiu, Chengxu; Zhou, Weixing; Long, Lin; Lv, Pengyi; Martynenko, Sergey; Yanovskiy, Leonid
Highlights: Using EHD technique to enhance avionics system heat dissipation is proposed. Electrical properties of aviation kerosene in wire-tube EHD structure are studied. Inlet parameters affecting the EHD heat transfer enhancement is investigated. Flow, temperature and electric fields are captured by numerical simulation. Abstract: Coolant heat transfer capacity determines the security of avionics system operation. Electrohydrodynamics (EHD), as an enhanced heat transfer technology, can be applied to the avionics cooling system. In this paper, the forced convection heat transfer characteristics of aviation kerosene enhanced by the EHD technique were investigated by both experimental and numerical simulation methods for the first time. One kind of wire-tube structure heat exchanger was designed and the heat dissipation performance of aviation kerosene was tested experimentally at different inlet parameters and electric potentials. A 3D mathematical model was established based on Maxwell and Navier-Stokes equations and the finite volume method was used for conservative discretization of the governing equations. The experimental and numerical simulation results are in good agreement. In the range from 128 to 900 of Reynolds number, the EHD heat transfer enhancement effect becomes weaken with the increase of mass flow. The charge migration along the electric field is suppressed due to the increasing axial velocity. However, the heat transfer enhancement effect is more obvious with the increasing inlet temperature of aviation kerosene. Due to the low viscosity and high ion mobility of high-temperature aviation kerosene, the charge migrating ability is enhanced and the viscous resistance is easier to overcome to produce the secondary flow. The maximum heat transfer enhancement ratio can reach 1.9 times. This paper expanded the EHD application to aviation fuels as the coolant in avionics systems and provided a deeper understanding on inlet parameters affecting the EHD heat transfer enhancement.